Optimization of process parameters on commercial mild steel using taguchi technique - Jaiganesh, V.; Yokesh Kumar, B.; Sevvel, P.; Balaji, A.J. (International Journal of Engineering and Technology, 2017)
In the present scenario of bulk manufacturing where Metal Removal Rate (MRR), Chip Thickness Ratio (CTR) and Surface Roughness (SR) is of significant importance in manufacturing the component using CNC (computer numerical controlled) machines. Nine experiments were conducted based on orthogonal array. General linear model has been generated for all the three output parameters such as (MRR, Chip Thickness Ratio surface roughness) versus input parameters (speed, time, depth of cut). The statistical method called the analysis of variance (ANOVA) is applied to find the critical factor. The Main effects of S/N ratio values are found and plotted in the form of graph. The optimized value is found for speed, time, and depth of cut by using â€œMINITABâ€ software. By using this optimized value the efficient metal cutting can be done in commercial mild steel.